Debates filosófico-políticos sobre Karl Marx en México después del “socialismo realmente existente”. Un análisis desde la filosofía - Valerio Miranda, David Alberto (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
This thesis is developed around the analysis of the philosophical-political debates carried out in Mexico on the theoretical work of Karl Marx. Among the discussions identified and analyzed, the research was limited to four: 1) The debate between Marxism and neo-liberalism centered on the question of the state. 2) The debate between Marxism and democracy. 3) The debate on Marxism hegemony and plurality and 4) The debate between Marxism and postmodernism centered on the question of Utopia. It should be noted that the present research was also limited to review only authors of Mexican nationality or based in Mexico who with production after 1989 (the end of "really existing socialism") participated or produced theoretical work written within the four debates mentioned above. This is intended to show the vision that has been developed of Marxism in Mexico in the last thirty years, in addition to observing the importance and legacy of the German theorist in the present context.

La presente tesis se desarrolla en torno al análisis de los debates filosófico-políticos realizados en México acerca de la obra teórica de Karl Marx. Dentro de las discusiones identificadas y analizadas la investigación se limitó a cuatro: 1) el debate entre el marxismo y el neoliberalismo centrado en la cuestión del Estado. 2) el debate entre el marxismo y la democracia. 3) el debate sobre marxismo hegemonía y pluralidad y 4) el debate entre marxismo y la posmodernidad centrado en la cuestión de la Utopía. Cabe destacar que la presente investigación también se limitó a revisar solo autores de nacionalidad mexicana o radicados en México que con producción posterior a 1989 (fin del “socialismo realmente existente”) participaron o produjeron obra teórica escrita dentro de los cuatro debates antes mencionados. Con esto se pretende mostrar la visión que se ha desarrollado del marxismo en el México de los últimos treinta años, además de observar la vigencia importancia y legado del teórico alemán en el contexto presente.
Instituto de Investigaciones Filosóficas. Facultad de Filosofía. Doctorado Institucional en Filosofía
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/8346; info:eu-repo/classification/cti/4; IIF-D-2022-0919; Marxismo; Neoliberalismo; Democracia